Manajemen Kepala Madrasah dalam Meningkatkan Kualitas Sarana dan Prasarana Pendidikan - Azom, Ismul; Muslih; Rianti, Ida (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
Adequate facilities and infrastructure are crucial factors in supporting an effective teaching and learning process; however, at MTs Nurul Huda, there are still several challenges, such as limited funding and inadequate facilities. This study aims to analyze the role of the principal in managing facilities and infrastructure at Madrasah Tsanawiyah Swasta Nurul Huda Muaro Jambi. The research method used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation. The obtained data are analyzed descriptively to provide an overview of the management practices of facilities and infrastructure at MTs Nurul Huda. The results show that the principal plays a central role in planning facility needs by involving teachers and the school committee to create a collaborative atmosphere. Additionally, the principal is directly involved in the procurement of facilities and ensures the quality and suitability of the facilities with the curriculum. Proactive maintenance and regular supervision are carried out to maintain the condition of the facilities, while encouraging active participation from the entire school community in maintaining them. Although challenges such as budget limitations and lack of participation from all parties exist, the principal strives to create a conducive learning environment. This study concludes that effective and collaborative leadership by the principal significantly impacts the improvement of education quality and the management of facilities and infrastructure at the madrasah. These findings can serve as a reference for other madrasahs in efforts to enhance the sustainable management of educational facilities.